2022
DOI: 10.3390/rs14061394
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Obukhov Length and Friction Velocity from Floating Lidar Observations: A Data Screening and Sensitivity Computation Approach

Abstract: This work presents a parametric-solver algorithm for estimating atmospheric stability and friction velocity from floating Doppler wind lidar (FDWL) observations close to the mast of IJmuiden in the North Sea. The focus of the study was two-fold: (i) to examine the sensitivity of the computational algorithm to the retrieved variables and derived stability classes (the latter through confusion-matrix theory), and (ii) to present data screening procedures for FDWLs and fixed reference instrumentation. The perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(39 citation statements)
references
References 50 publications
(75 reference statements)
1
38
0
Order By: Relevance
“…During the last decade, floating Doppler wind lidars (FDWLs) have emerged as the wind-energy-industry preferred solution to replace the metmast because of their accuracy and attractive cost-benefit of installation and maintenance. Many studies have shown that 10 min averaged wind-speed measurements from FDWLs are numerically equivalent to reference observations from anemometers or fixed Doppler wind lidar (DWL) [4][5][6]. However, FDWLs cannot measure a number of the atmospheric parameters that instruments mounted on meteorological masts can, which restrains commercial acceptance of FDWLs as stand-alone sensing instrument.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…During the last decade, floating Doppler wind lidars (FDWLs) have emerged as the wind-energy-industry preferred solution to replace the metmast because of their accuracy and attractive cost-benefit of installation and maintenance. Many studies have shown that 10 min averaged wind-speed measurements from FDWLs are numerically equivalent to reference observations from anemometers or fixed Doppler wind lidar (DWL) [4][5][6]. However, FDWLs cannot measure a number of the atmospheric parameters that instruments mounted on meteorological masts can, which restrains commercial acceptance of FDWLs as stand-alone sensing instrument.…”
Section: Introductionmentioning
confidence: 99%
“…Other sensors can provide air-pressure and air-humidity observations. However, alternative methods are needed in scenarios with limited instrumentation [5,[15][16][17][18][19][20]. A good number of these methods use Monin-Obukhov similarity theory (MOST).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations